2023
DOI: 10.1590/1984-0462/2023/41/2021235
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to different methods for introducing complementary food to 7-month-old babies: a randomized clinical trial

Abstract: Objective: To assess the adherence to three methods of food introduction for 7-month-old babies. Methods: This is a randomized clinical trial conducted with mother-infant pairs, submitted to the intervention with five and a half months of age and three different methods for food introduction according to randomization: Parent-Led Weaning (PLW), Baby-Led Introduction to SolidS (BLISS), or mixed (specially developed for this study). Adherence to the method was assessed at the seventh month of age, via telephone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Preliminary data demonstrate that this approach has greater adherence compared to PLW and BLISS. 26 Therefore, this can be a safe approach to be guided, especially regarding the risk of suffocation.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data demonstrate that this approach has greater adherence compared to PLW and BLISS. 26 Therefore, this can be a safe approach to be guided, especially regarding the risk of suffocation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study limitation is the limited adherence to the proposed methods in randomization. Our results showed that approximately 30% of the children continued to follow the recommended method 24 , 25 . In general, families showed greater adherence to the mixed method, which combined both techniques (PLW and BLISS).…”
Section: Discussionmentioning
confidence: 60%
“…). O ensaio clínico randomizado realizado em 2023, que buscou comparar o adesão aos métodos BLISS, PLW e o misto, concluiu que, na visão dos pais, a proposta de autonomia do Brazilian Journal of Health Review, Curitiba, v. 6, n. 4, p.18166-18182, jul/aug., 2023 bebê é visto como um ponto negativo dessas abordagens, já que o eles perdem o controle sobre a quantidade de alimento ingerido(MOREIRA, et al, 2023).Ademais, os métodos guiados pelo bebê proporcionam refeições em conjunto com a família, com maior compatibilidade entre os alimentos ingeridos pelos demais membros quando comparado a abordagem PLW. Com isso, o BLW e BLISS apresentam uma proposta acessível às famílias com estilo de vida acelerado, as quais têm dificuldade no preparo de duas refeições diferentes e, portanto, a adesão a esse método pode ser intensificada(ARANTES, et al, 2018).Em contraste, Vieira et al, a partir de um estudo quantitativo descritivo observou a escolha do método de acordo com as características sociodemográficas de cada família e observou não haver diferença significativa entre as abordagens, exceto pelo fato das mães que adotaram o BLW apresentarem menor proporção de trabalho remunerado e serem mais jovens(VIEIRA, et al, 2020).…”
unclassified